COGNITIVE COMPETENCIES IN DIGITAL ENGLISH READING: A SYSTEMATIC REVIEW - Situmorang, Rayhan Khairunnisa; Sulistyaningrum, Siti Drivoka (Universitas Muhammadiyah Metro, 2024)
The rise of digital devices and content consumption has reshaped reading habits, potentially influencing the development of early reading skills. However, limited research addresses cognitive competencies in digital English reading, which enable readers to process, comprehend, and retain information online. This study aimed to investigate the presence of cognitive competencies in digital English reading materials and the challenges in developing them. A Systematic Literature Review (SLR) was conducted, excluding 47 articles and including 15 based on research criteria. Findings indicate that while cognitive competencies—such as critical thinking, problem-solving, creativity and innovation, situation analysis, decision-making, and pattern recognition—are integrated into English reading materials, they require further development in digital contexts. The study also identified challenges in developing cognitive competence, including cognitive load, material and pedagogical design, teacher and student expectations, technology and digital literacy, feedback and assessment, information overload, interdisciplinary and critical thinking skills, and the nature of literacy. Understanding the integration of cognitive competencies into digital resources is crucial for educators and stakeholders, as it aids in optimizing language learning experiences and developing targeted solutions to enhance language learning tools and strategies.